2017
DOI: 10.4172/2155-6148.1000804
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of Bedside Upper Airway Ultrasonography vs. Standard Auscultation for Assuring the Location of Endotracheal Tube after Tracheal Intubation: Comparative Study Controlled by Quantitative Waveform Capnography

Abstract: Objectives: To estimate the accuracy and rapidity of bed-side upper airway ultrasonography (UA-US) versus standard auscultation (SA) for confirmation of endotracheal tube (ETT) position. Patients and methods:107 patients underwent tracheal intubation for maintenance of general anesthesia. Position of ETT was confirmed by chest auscultation for the presence of breath sounds on both sides, and by UA-US using 9-12 MHz linear US transducer that was placed transversely on the neck anteriorly and superior to the sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Sun JT et al(2014) found that the sensitivity, specificity, positive predictive value, and negative predictive value of tracheal ultrasonography were 98.9%, 100%, 100%, and 85.7%, respectively. Arafa S et al (2018) found that the sensitivity, specificity and accuracy rates of 97%, 71.4% and 95.3%. Lahham S et al (2018) found that the trachea with 96.4% sensitivity and 33.3% specificity.…”
Section: Discussionmentioning
confidence: 95%
“…Sun JT et al(2014) found that the sensitivity, specificity, positive predictive value, and negative predictive value of tracheal ultrasonography were 98.9%, 100%, 100%, and 85.7%, respectively. Arafa S et al (2018) found that the sensitivity, specificity and accuracy rates of 97%, 71.4% and 95.3%. Lahham S et al (2018) found that the trachea with 96.4% sensitivity and 33.3% specificity.…”
Section: Discussionmentioning
confidence: 95%
“…Confirmation of the correct ETT placement should be rapidly done for early detection of improper positions to prevent fatal consequences (Arafa, Abouzkry, & Mohamady, 2018). The confirmation methods differ according to the hospital setting.…”
Section: Section Ii: Factors Affecting Ett Nursing Carementioning
confidence: 99%